Academic Hardiness in Students with Leukimia at SMA Terbuka Gambut - Rika Vira Zwagery (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2021)
This research aims to determine the academic hardiness in leukimia student. Academic hardiness is a resilient personality and strength in dealing with all academic difficulties that pressure students. The research subject was conducted on a High School Student at Sekolah Terbuka who had Leukimia. The Research method used Qualititative methods to provide an overview of academic hardiness. This study used observation and interview techniques. The results found that although the subject is a cancer patient who has limitations but he has an Academic Hardiness because it has good social support from parents and positive self-perception